Pengaruh Literasi Gizi Terhadap Perilaku Makan Ibu Hamil: Literature Review - Nadhira Silmi Alifa; Evi Martha (Lembaga Pengembangan Kinerja Dosen, 2025)
Nutritional problems in pregnant women are still a public health issue that needs serious attention in Indonesia. One of the factors that influence the nutritional status of pregnant women is eating behavior, which is also influenced by the level of nutritional literacy. Nutrition literacy includes the ability to access, understand, evaluate, and apply nutritional information in everyday life. This study aims to examine the relationship between nutritional literacy and eating behavior of pregnant women through the Systematic Literature Review approach by following the Prisma guidelines. Literature sources are obtained from Google Scholar and Pubmed, published in the range of 2020-2025, and selected based on inclusion and exclusion criteria. A total of five relevant articles have been analyzed descriptively. The results of the study show that the majority of pregnant women have a low level of nutritional literacy, which is often in line with the low quality of food intake and compliance with nutrition recommendations. However, no explicit evidence was found about the direct influence of nutritional literacy on eating behavior. In addition, the awareness of individual pregnant women also plays an important role in actualizing nutritional information into a healthy eating practice. Therefore, increased nutritional literacy must be accompanied by efforts to build awareness and motivation of pregnant women through consistent and contextual education of health workers and other related parties.